Em torno do dispositivo comunicacional: uma abordagem cognitivo-discursiva da enunciação na página do Facebook Quebrando o tabu - Rezende, Breno Rafael Martins Parreira Rodrigues (2022)
In this doctoral research, wich i carried out in the Postgraduate Program in Linguistic Studies ar the Institute of Letters and Linguistics at the Federal University of Uberlândia, I aimed to demonstrate the productivity of adding a cognitive dimension to discursive analysis. To do so, I analyzed a corpus, consisting of publications and comments, collected on a page of the social network Facebook: Quebrando o tabu. I was able to verify that the enunciation on the page is trigged and managed by a communicational device os multiple dimensions, constituted by the hypergenericity system and médium, each one operating simultaneously on it with different constraints, in order to, respectively, establish na maitain the semantic identity of the page and to license violent verbal manifestations in the interactions that occur in it. In addition, I reread, in the light of the Distributed Cognition approach (HUTCHINS, 1995a, 1995b, 2002), the notion of communicational device, taking it as a tool of a cognitive-discursive nature (NORMAN, 1991; PAVEAU, 2013). ; MUSSALIM, 2018b) and participates in a cognitive-distributed system in which various inputs (the functioning of the communication device and the interaction between subjects) contribute to the manifestation of the same output: the establishment of discussions, which promote and maintain a scenography of a “discussion forum”, which gives identity to the Quebrando o Tabu page on Facebook. Additionaly, considering the concept of pre-discourse (PAVEAU, 2013), I analyzed these 'arguments', established through the comments received by the page, which thematized the question of “what is family”, demonstrating that they are fed by distinct sociocognitive frames. The conclusion of this analysis pointed out that what is debated in the argument stems from the stabilization/destabilization movement of a pre-discourse that, over time, conquered hegemony around the issue, building the worldview that “family” it is an institution made up of cis-gender men and women and their children, which is challenged by another frame that feeds the discursive production on the page, according to which “family is diversity”. As a conclusion, I was able to sustain that the re-reading I proceeded with the notion of communicational device, considering it as a tool of a cognitive-discursive nature, produces theoretical-methodological-analytical gain, since, in addition to allowing us to understand issues related to to enunciation, it also sheds light on relevant cultural issues, among them, how socio-cognitive frameworks are produced and propagated, which, ultimately, because they are products of culture (of collective frameworks of knowledge, values, beliefs and practices), make it possible to understand the functioning of what, in this thesis, we refer to as cultural devices.